Site-specific DNA Inversion by Serine Recombinases - Johnson, Reid C. (Microbiol Spectr, 2015)
Reversible site-specific DNA inversion reactions are widely distributed in bacteria and their viruses. They control a range of biological reactions that most often involve alterations of molecules on the surface of cells or phage. These programmed DNA rearrangements usually occur at a low frequency, thereby preadapting a small subset of the population to a change in environmental conditions, or in the case of phages, an expanded host range. A dedicated recombinase, sometimes with the aid of additional regulatory or DNA architectural proteins, catalyzes the inversion of DNA. RecA or other components of the general recombination-repair machinery are not involved. This chapter discusses site-specific DNA inversion reactions mediated by the serine recombinase family of enzymes and focuses on the extensively studied serine DNA invertases that are stringently controlled by the Fis-bound enhancer regulatory system. The first section summarizes biological features and general properties of inversion reactions by the Fis/enhancer-dependent serine invertases and the recently described serine DNA invertases in Bacteroides. Mechanistic studies of reactions catalyzed by the Hin and Gin invertases are then discussed in more depth, particularly with regards to recent advances in our understanding of the function of the Fis/enhancer regulatory system, the assembly of the active recombination complex (invertasome) containing the Fis/enhancer, and the process of DNA strand exchange by rotation of synapsed subunit pairs within the invertasome. The role of DNA topological forces that function in concert with the Fis/enhancer controlling element in specifying the overwhelming bias for DNA inversion over deletion and intermolecular recombination is emphasized.